(untitled) (Journal of Universal Science Research, 2023)
Physical qualities play a vital role in the performance and success of athletes across various sports disciplines. The identification and evaluation of these physical qualities are crucial for athletes, coaches, and sports scientists to design effective training programs and optimize athletic performance. Athletes across various sports rely on their physical qualities to excel in their respective disciplines. The development of these physical qualities plays a crucial role in maximizing performance potential. This article explores the importance of key physical qualities in athletes and provides an overview of the methodologies employed to enhance these qualities. This abstract provides an overview of the physical qualities commonly assessed in athletes and the methodologies used for their evaluation.